2015
DOI: 10.1016/j.celrep.2015.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Axis Patterning by BMPs: Cnidarian Network Reveals Evolutionary Constraints

Abstract: SummaryBMP signaling plays a crucial role in the establishment of the dorso-ventral body axis in bilaterally symmetric animals. However, the topologies of the bone morphogenetic protein (BMP) signaling networks vary drastically in different animal groups, raising questions about the evolutionary constraints and evolvability of BMP signaling systems. Using loss-of-function analysis and mathematical modeling, we show that two signaling centers expressing different BMPs and BMP antagonists maintain the secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
137
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(184 citation statements)
references
References 39 publications
8
137
0
Order By: Relevance
“…We find that scatter search efficiently and effectively explores the parameter space, and that low temperature simulated annealing turns good solutions into excellent ones. These results suggest that it is a promising method for inferring unknown networks, such as the one laying down the body plan of the sea anemone Nematostella vectensis [17,39,40], where multiple rounds of exploration are likely necessary. Moreover, given the additional computational costs for simulating systems in which morphogenetic processes play an important role (e.g., 2D and 3D models including cell migration, tissue rearrangements, growth, cell death) a light explorative method will be a prerequisite for success.…”
Section: Introductionmentioning
confidence: 99%
“…We find that scatter search efficiently and effectively explores the parameter space, and that low temperature simulated annealing turns good solutions into excellent ones. These results suggest that it is a promising method for inferring unknown networks, such as the one laying down the body plan of the sea anemone Nematostella vectensis [17,39,40], where multiple rounds of exploration are likely necessary. Moreover, given the additional computational costs for simulating systems in which morphogenetic processes play an important role (e.g., 2D and 3D models including cell migration, tissue rearrangements, growth, cell death) a light explorative method will be a prerequisite for success.…”
Section: Introductionmentioning
confidence: 99%
“…Chordin is expressed where BMP signaling is low and coincides with the expression of Nematostella Dpp and BMP5-8 ( Fig. 4; Genikhovich et al, 2015). Similarly, in Xenopus, the dorsal side expresses Chordin, BMP2, and ADMP (ADMP stands for the divergent BMP antidorsalizing morphogenetic protein; Moos, Wang, & Krinks, 1995).…”
Section: The Ancestral Chordin/bmp Morphogenetic Pathwaymentioning
confidence: 99%
“…Sizzled, which plays a very prominent role in the Xenopus and zebrafish ventral gastrula centers, is not present in Nematostella or, to our knowledge, in any invertebrate. Knockdown experiments in sea anemone embryos showed that Chordin expression is the main determinant of where the low BMP side is formed, and mathematical modeling showed that Tolloid and Chordin are the rate-limiting elements in establishing the BMP gradient (Genikhovich et al, 2015). Different animals use variations of the ancestral BMP/Chordin/ Tolloid D-V module.…”
Section: The Ancestral Chordin/bmp Morphogenetic Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…The reported experiments have explicitly shown the real possibility to change the body form along the lines of transformed coordinates suggested by D'Arcy Thompson by modifying the gradient of Chordin/ Tolloid/BMP. The Chordin/Tolloid/ BMP pathway patterns the embryos of many organisms, including prebilaterian diploblasts such as the sea anemone Nematostella vectensis, in which Chordin and Tolloid, like in Xenopus, maintain stable BMP gradient, suggesting this pathway is an ancestral network allowing modification of the animal form in evolution, as well (Genikhovich et al, 2015).…”
Section: On "Growth and Form" And Asapbio Reformmentioning
confidence: 99%